2011
DOI: 10.1093/chrsci/49.8.634
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Stability Indicating Method for the Determination of Exemestane by Reverse Phase High Performance Liquid Chromatography

Abstract: Exemestane is an aromatase inhibitor used in the treatment of breast cancer. A selective stability-indicating reversed-phase high performance liquid chromatography (RP-HPLC) method has been developed which can separate and accurately quantitate low levels of exemestane. The stability-indicating capability of the method was demonstrated by adequate separation of exemestane and all the degradation product peaks from exemestane peak and also from each other in stability samples of exemestane. Chromatographic sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The individual quantification of EXE by the HPLC method has been reported at various wavelengths, such as 242, 247, 249, and 250 nm, in the literature. Likewise, the individual quantification of THY has been reported at 250 and 254 nm. , In our method, during the scanning, the maximum wavelength of detection was found to be 244 nm for EXE and 253 nm for THY, respectively. Therefore, to mitigate the hurdles associated with the previously reported methods, we have developed an efficient and validated method as per the ICH guidelines for the simultaneous estimation of EXE and THY on 243 nm wavelength in considering to achieve optimum sensitivities for both compounds.…”
Section: Introductionsupporting
confidence: 54%
“…The individual quantification of EXE by the HPLC method has been reported at various wavelengths, such as 242, 247, 249, and 250 nm, in the literature. Likewise, the individual quantification of THY has been reported at 250 and 254 nm. , In our method, during the scanning, the maximum wavelength of detection was found to be 244 nm for EXE and 253 nm for THY, respectively. Therefore, to mitigate the hurdles associated with the previously reported methods, we have developed an efficient and validated method as per the ICH guidelines for the simultaneous estimation of EXE and THY on 243 nm wavelength in considering to achieve optimum sensitivities for both compounds.…”
Section: Introductionsupporting
confidence: 54%
“…EXE concentration was quantified with the reversed-phase high-performance liquid chromatography apparatus (RP-HPLC; Shimadzu, Tokyo, Japan) attached to the UV detector. The RP-HPLC technique was reproduced as per the published report by Konda et al [26]. A C-18 column (Li Chospher 100; 250×4.6 mm dimension with 5 μm particle size) was employed for the chromatographic separation at 30 °C.…”
Section: Quantification Of Exe In Exe-tpgs-plhnpsmentioning
confidence: 99%
“…Till now only two stability indicating HPLC methods are available in the literature in which Bharath et al [20] developed a stability indicating method in which UV detector was used and the retention time of Exemestane was at around 7.0 minutes. Mathrusri Annapurna et al [21] observed the elution of Exemestane at about 4.5 minutes using phosphate buffer and acetonitrile mixture. In the present study the authors have proposed a new simple, economical and robust stability indicating liquid chromatographic method (Isocratic mode) for the determination of Exemestane in pharmaceutical dosage forms (Tablets).…”
Section: Breda Et Al Developed a Hplc Methods In Plasma By Highperfor...mentioning
confidence: 99%